Numerical Optimisation of Mould and Injection Moulding Process: Case Study - Damir Godec; Mislav Sever; Mislav Tujmer; Bruno Krajačić (Tehnički Glasnik)
The paper presents the optimisation of mould for injection moulding as well as injection moulding process parameters using numerical computer simulation in the Moldex3D software package. The optimisation process will be applied to a specific moulded part – branching terminal block – and an already manufactured mould. The paper includes evaluation of the existing mould for injection moulding designed and manufactured without application of numerical simulation of injection moulding process. According to the shortcomings found out in evaluation process, by application of numerical simulation of injection moulding process, the optimisation of the mould design was conducted in several stages to achieve as optimal as possible moulded part quality and injection moulding process parameters without dramatic changes in already manufactured mould.